2022
DOI: 10.3389/fonc.2022.826617
|View full text |Cite
|
Sign up to set email alerts
|

RelA Is an Essential Target for Enhancing Cellular Responses to the DNA Repair/Ref-1 Redox Signaling Protein and Restoring Perturbated Cellular Redox Homeostasis in Mouse PDAC Cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers with a poor response to current treatment regimens. The multifunctional DNA repair-redox signaling protein Ref-1 has a redox signaling function that activates several transcriptional factors (TFs) including NF-κB (RelA), STAT3, AP-1. These have been implicated in signaling in PDAC and associated with cancer progression and therapy resistance. Numerous studies have shown a role for RelA in PDAC inflammatory responses and therapy resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The redox function of APE1/Ref-1 has been studied as an important aspect in protecting cells from oxidative stress [ 11 , 35 ]. Specific inhibition of redox activity of APE1/Ref-1 by E3330, a redox inhibitor of APE1/Ref-1, enhanced ROS production [ 36 , 37 ]. In this study, we demonstrated that the anti-adipogenic effect of APE1/Ref-1 could be mediated by the inhibition of expression of adipogenic transcriptional factors such as C/EBP-α and PPAR-γ .…”
Section: Discussionmentioning
confidence: 99%
“…The redox function of APE1/Ref-1 has been studied as an important aspect in protecting cells from oxidative stress [ 11 , 35 ]. Specific inhibition of redox activity of APE1/Ref-1 by E3330, a redox inhibitor of APE1/Ref-1, enhanced ROS production [ 36 , 37 ]. In this study, we demonstrated that the anti-adipogenic effect of APE1/Ref-1 could be mediated by the inhibition of expression of adipogenic transcriptional factors such as C/EBP-α and PPAR-γ .…”
Section: Discussionmentioning
confidence: 99%
“…HRECs were lysed in RIPA extraction buffer supplemented with protease and phosphatase inhibitors (Santa Cruz Biotechnology, Santa Cruz, CA, USA) [ 83 ]. Denatured samples (20 μg) were subjected to SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…At least three independent experiments were performed. Relative quantity was determined using the 2 −ΔΔCt method as previously published [ 83 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the inhibitor degrades, NF-kappa-B migrates to the nucleus, regulating the transcriptional activities. [6][7][8] It has been demonstrated that RELA is the transcription factor of liver X receptor alpha, which is upregulated in gastric cancer. RELA appears to have a dual role in gastric cancer cells, promoting differentiation while simultaneously suppressing proliferation and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In the cytoplasm, however, NF‐kappa‐B is inactive due to the role of inhibitors. As the inhibitor degrades, NF‐kappa‐B migrates to the nucleus, regulating the transcriptional activities 6–8 . It has been demonstrated that RELA is the transcription factor of liver X receptor alpha, which is upregulated in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%